Factors Expressed by Murine Embryonic Pancreatic Mesenchyme Enhance Generation of Insulin-Producing Cells From hESCs - Guo, Tingxia (American Diabetes Association, 2013)
Islet transplantation has proven to be a successful strategy to restore normoglycemia in patients with type 1 diabetes (T1D). However, the dearth of cadaveric islets available for transplantation hampers the widespread application of this treatment option. Although human embryonic stem cells and induced pluripotent stem cells are capable of generating insulin-producing cells in vitro when provided with the appropriate inductive cues, the insulin-expressing cells that develop behave more like immature β-cells with minimal sensitivity to glucose stimulation. Here, we identify a set of signaling factors expressed in mouse embryonic mesenchyme during the time when foregut and pancreatic progenitors are specified and test their activities during in vitro differentiation of human embryonic stem cells. Several of the identified factors work in concert to expand the pancreatic progenitor pool. Interestingly, transforming growth factor (TGF)-β ligands, most potent in inducing pancreatic progenitors, display strong inhibitory effects on subsequent endocrine cell differentiation. Treatment with TGF-β ligands, followed by the addition of a TGF-β receptor antagonist, dramatically increased the number of insulin-producing cells in vitro, demonstrating the need for dynamic temporal regulation of TGF-β signaling during in vitro differentiation. These studies illustrate the need to precisely mimic the in vivo conditions to fully recapitulate pancreatic lineage specification in vitro.